PENGARUH SHOPEE PAYLATER DAN FLASH SALE TERHADAP IMPLUSE BUYING MAHASISWA DI MARKETPLACE SHOPEE - Onsardi, Onsardi; Rosalina, Viona (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The study aims to examine the effect of shopee PayLater on students’ impluse buying among Management students at Universitas Muhammadiyah Bengkulu in the Shopee marketplace. It also seeks to determine the effect of flash sale on students’impluse buying and to analyze the combined influence of Shopee PayLater and flash sale on students’ impluse buying behavior. This reserch employed a quantitative approach, which was used to study a specific population and sample. Based on the findings, the simultaneous effect of Shopee PayLater and flash sale on the students’ impluse buying in the Shopee marketplace among Management students at Universitas Muhammadiyah Bengkulu can be concluded as follows:1. Shopee PayLater (X1) has a positive and significant effect on impluse buying (Y) in the Shopee marketplace among Management students at Universitas Muhammadiyah Bengkulu. This means that the higher the use of Shopee PayLater, the greater the tendency for impluse buying. 2. Flash sale (X2) have an effect on impluse buying (Y) in the Shopee marketplace among Management students at Universitas Muhammadiyah Bengkulu. This indicates that the higher the frequency of flash sale, the more it increases impluse buying behavior. 3. Shopee PayLater and flash sale jointly influence impluse buying in the Shopee marketplace among Management students at Universitas Muhammadiyah Bengkulu, With an F significance value of 0.000<0.05, confirming a significant combined effect. Keywords: Shopee Paylater, Flash Sale, Impluse Buying